Epithelioid trophoblastic tumor of uterus presenting as an ovarian mass: A diagnostic and therapeutic dilemma - Shet Tanuja; Parage Mahendra; Maheshwari Amita; Nair Reena; Gupta Sudeep; Tongaonkar Hemant; Chinoy Roshan (Wolters Kluwer Medknow Publications, 2008)
Epithelioid trophoblastic tumor (ETT) is a rare gestational trophoblastic tumor and often poses a diagnostic and therapeutic challenge to the involved clinicians. We report a case of epithelioid trophoblastic tumor in a young woman which involved the uterus, parametrium and the right ovary. Misdiagnosis as a choriocarcinoma led to improper treatment and progressive disease. Microscopically it revealed a relatively monotonous population of epithelioid cells arranged in nests with hyaline-like matrix surrounding the tumor cells. Differential diagnosis between placental site trophoblastic tumor and carcinoma was ruled out based on histology and immunohistochemistry. The patient developed lung and brain metastasis after 10 months and is alive with disease 1½ years thereafter and is taking palliative chemotherapy. The patient had β-HCG level of 85.1 mIU/mL at the time of diagnosis; but just before metastasis, the levels rose. Awareness of the histological features of ETT is essential to avoid misdiagnosis, as it represents a tumor which is primarily treated by surgery rather than with chemotherapy.